PENYULUHAN KIAT UNTUK MEMULAI USAHA BARU KEPADA PENGURUS BADAN KESWADAYAAN MASYARAKAT (BKM) DAMAI SEJAHTERA - Mislan Sihite; Rasmulia Sembiring; Robinhot Gultom; Sahat Parulian Remus Silalahi; Siti Normi; Saur Melianna; Tiur Rajagukguk; Winarto Winarto; Sondang Ni Bulan Marbun; Rommel Sitohang; Selamat Siregar; Toman Panggabean (Universitas Methodist Indonesia, 2022)
Community Service is one of the Tri Dharma of Higher Education and this activity is very beneficial to the community and to the lecturers who carry out these activities. The Lecturers of the Faculty of Economics, Management Study Program carried out this activity at the Damai Prosperous Community Self-Reliance Agency (BKM) in Sukaraja Village - Medan Maimun District with the topic